Determination of 3‑Alkyl-2-methoxypyrazines in Green Coffee: A Study To Unravel Their Role on Coffee Quality - Mutarutwa, Delvana; Navarini, Luciano; Lonzarich, Valentina; Crisafulli, Paola; Compagnone, Dario; Pittia, Paola (Journal of agricultural and food chemistry, 2020)
Although a high concentration of some 3-alkyl-2-methoxypyrazines in green coffee has been associated with an off-flavor described as potato taste defect (PTD) or “peasy” defect, affecting the product quality, the natural concentration of these compounds in good quality coffee beans has never been the subject of a detailed study. 3-Isobutyl-2-methoxypyrazine (1), 3-sec-butyl-2-methoxypyrazine (2), 3-isopropyl-2-methoxypyrazine (3) concentrations were determined on a range of selected, good quality green coffees of different botanical species (arabica and robusta) and geographical origin. The presence of the three methoxypirazines was confirmed in all samples; the concentration of compound 1 was significantly higher than those of compounds 3 and 2, showing a geographical-origin-dependent variability. This whole set of experimental data was then used as a reference to ascertain the PTD occurrence in “suspected PTD” and insect-damaged samples. Compound 3 was the main indicator of defectiveness, with a main variability in its concentration in insect-damaged samples, suggesting that the insect-induced damage is not a sufficient condition to induce the off-flavor. The analysis in fresh potatoes, carried out to disclose the origin of the term used to describe the PTD in coffee, showed a very low concentration of 3-alkyl-2-methoxypyrazines. However, the relative prevalence of compound 3 on the total of 3-alkyl-2-methoxypyrazines could be related to the characteristic “potato” flavor frequently evoked to describe the sensory perceived defect in coffee.